2014
DOI: 10.1007/s00726-014-1679-1
|View full text |Cite
|
Sign up to set email alerts
|

Moderate swimming exercise and caffeine supplementation reduce the levels of inflammatory cytokines without causing oxidative stress in tissues of middle-aged rats

Abstract: The levels of circulatory inflammatory markers, including interleukin (IL) IL-1β, IL-6, tumor necrosis factor-α (TNF-α) and interferon (INF-γ), are known to increase associated to aging. Caffeine has been reported to produce many beneficial effects for health. Exercise is considered to be a safe medicine to attenuate inflammation and cellular senescence. The purpose of the present study was to investigate the effects of a moderate-intensity swimming exercise (3 % of body weight, 20 min per day, 4 weeks) and su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
25
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 45 publications
3
25
0
3
Order By: Relevance
“…Such related effects may have, in turn, helped reducing the TBARS expression observed in CG. Cechella et al (2014) observed that swimming and caffeine supplementation in middle-aged rats led to reduced glutathione in the gastrocnemius muscles and in the liver of the animals. It reduced the oxidative stress in these tissues, similar to what was observed in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Such related effects may have, in turn, helped reducing the TBARS expression observed in CG. Cechella et al (2014) observed that swimming and caffeine supplementation in middle-aged rats led to reduced glutathione in the gastrocnemius muscles and in the liver of the animals. It reduced the oxidative stress in these tissues, similar to what was observed in the current study.…”
Section: Discussionmentioning
confidence: 96%
“…Caffeine is classified as part of the methylxanthine family of drugs (Cechella et al, 2014;Mohr, Nielsen, Bangsbo, 2011) and is extensively consumed by athletes as an ergogenic aid (Backhouse et al, 2011;Mohr, Nielsen, Bangsbo, 2011) since its removal from the World AntiDoping Agency (WADA) prohibited list of substances (Backhouse et al, 2011;Mohr, Nielsen, Bangsbo, 2011). According to the Medical Council of International Olympic Committee (IOC), caffeine is allowed in sports as long as its urinary excretion level is below 12 µg/mL (Bell, Jacobs, Ellerington, 2001).…”
Section: Introductionmentioning
confidence: 99%
“…In the U.S.A., adults ingest an average of 3 mg/kg of caffeine daily in coffee, tea, caffeinated sodas, and many other drinks and food (Sökmen et al, 2008). The popularity of caffeine as an ergogenic aide has increased dramatically over the last decade (Hendrix et al, 2010), Caffeine is the most widely consumed to improve cognitive, physical performance during exercise and has become a popular ergogenic aid among recreational and competitive athletes (Hendrix et al, 2010;Sökmen et al, 2008;Zheng et al, 2014).Caffeine is classified as part of the methylxanthine family of drugs (Cechella et al, 2014;Mohr, Nielsen, Bangsbo, 2011) and is extensively consumed by athletes as an ergogenic aid (Backhouse et al, 2011;Mohr, Nielsen, Bangsbo, 2011) since its removal from the World AntiDoping Agency (WADA) prohibited list of substances (Backhouse et al, 2011;Mohr, Nielsen, Bangsbo, 2011). According to the Medical Council of International Olympic Committee (IOC), caffeine is allowed in sports as long as its urinary excretion level is below 12 µg/mL (Bell, Jacobs, Ellerington, 2001).…”
mentioning
confidence: 99%
“…In general, exercise can exclusively affect cytokine levels depending on exercise type, duration, and intensity [21,26] . Several exercise protocols performed in animals or humans have reported different findings regarding cytokine levels [15,[27][28][29][30][31] . Mechanical stimulation of some tissues such as muscle, vascular smooth muscle, connective tissue, and bone leads to change in TGF-β1 production.…”
Section: Discussionmentioning
confidence: 99%
“…It seems like TGF-β1 levels transiently increase at the beginning of the exercise regimen and then normalization occurs due to the adaptation [32] . It has also been determined that exercise led to a reduction in TNF-α by stimulating IL-6 levels and increase in IL-1ra and IL-10 and antioxidant levels [22,[27][28][29][30] . On the other hand, there is evidence that moderate and overtraining swimming exercise does not induce any significant differences in TNF-α and IL-6 levels, but moderate exercise decreases TBARS levels in rats, suggesting that the intensive exercise periods or overtraining may not cause detrimental effects which consistent with our results [31] .…”
Section: Discussionmentioning
confidence: 99%